Avoiding impacts on biodiversity through strengthening the first stage of the mitigation hierarchy. Issue 2 (11th January 2017) - Phalan, Ben; Hayes, Genevieve; Brooks, Sharon; Marsh, David; Howard, Pippa; Costelloe, Brendan; Vira, Bhaskar; Kowalska, Aida; Whitaker, Samir
Abstract: The mitigation hierarchy is a decision-making framework designed to address impacts on biodiversity and ecosystem services through first seeking to avoid impacts wherever possible, then minimizing or restoring impacts, and finally by offsetting any unavoidable impacts. Avoiding impacts is seen by many as the most certain and effective way of managing harm to biodiversity, and its position as the first stage of the mitigation hierarchy indicates that it should be prioritized ahead of other stages. However, despite an abundance of legislative and voluntary requirements, there is often a failure to avoid impacts. We discuss reasons for this failure and outline some possible solutions. We highlight the key roles that can be played by conservation organizations in cultivating political will, holding decision makers accountable to the law, improving the processes of impact assessment and avoidance, building capacity, and providing technical knowledge. A renewed focus on impact avoidance as the foundation of the mitigation hierarchy could help to limit the impacts on biodiversity of large-scale developments in energy, infrastructure, agriculture and other sectors.